2020
DOI: 10.1039/c9py01442j
|View full text |Cite
|
Sign up to set email alerts
|

The generation of stabilized supramolecular nanorods from star-shaped polyglutamates

Abstract: We developed a new strategy of polyglutamate nanorod preparation based on supramolecular polymers stabilized with hydrophobic drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…6A), most probably consisting of doublehelical fibers, similar to a previously reported compound with an FFF core and ten glutamic residues per arm. 29 At pH 3.0, we observed various distinct morphologies, including separate fibers, parallel fiber doublets, short flat objects, and twisted nanoribbons consisting of multiple interacting fibers (Fig. 6B).…”
Section: Nanoribbon Formationmentioning
confidence: 89%
See 1 more Smart Citation
“…6A), most probably consisting of doublehelical fibers, similar to a previously reported compound with an FFF core and ten glutamic residues per arm. 29 At pH 3.0, we observed various distinct morphologies, including separate fibers, parallel fiber doublets, short flat objects, and twisted nanoribbons consisting of multiple interacting fibers (Fig. 6B).…”
Section: Nanoribbon Formationmentioning
confidence: 89%
“…Recent studies have reported that, upon closer examination, at least some nanofibers in aqueous solutions comprise two smaller fibers, either twisted or parallel. 28,29 Furthermore, several studies have reported the formation of more complicated structures (e.g., nanoribbons or triple helices) during the self-assembly of BTAbased molecules in organic solvents or their mixtures with water. [30][31][32] In water, stepwise self-assembly into clearly defined double helical nanorods was reported only for BTA-based Aucontaining metalloamphiphiles.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by a recent report of Zagorodko et al., who reported the formation of SPBs based on the BTP motif with three amino acid units per arm, we further increased the number of H‐bonds to identify the critical step for the formation of SPBs in our system. [ 35 ] For this purpose, we synthesized compound 2 comprising two leucine units per arm (Schemes S3 and S5, Supporting Information). We deliberately chose leucine in this case due to its sufficient hydrophobicity to shield the core H‐bonds compared to alanine.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the solvent was removed under reduced pressure yielding a highly viscous yellowish polymer. Yield: 995.3 mg (71%); 1 H-NMR (300 MHz, CDCl 3 , δ): 1.43 (s, 9H), 3.01 (br, 2H), 3.28 (br, 2H), 3.51 (br, 4H), 3.58 (br, 4H), 5.50 ppm (br, 1H); 31 carbamate)phosphazene and formation of the macroinitiator P1 was performed according to adapted literature procedure. [29,30] Briefly, the polymer (304.4 mg, 0.5641 mmol, 1 equiv.)…”
Section: Synthesis Of Poly(tert-butyl N-(2-[2-(2-aminoethoxy)ethoxy]e...mentioning
confidence: 99%
“…Vicent et al improved this aspect in the form of star‐branched PGAs, showing increased plasma half‐life time ( t 1/2 ) and cell uptake enhancement. [ 30 ] This has led to the development of different nanostructures, for example, self‐assembled nanorods [ 31 ] and sphere‐like cross‐linked nanocarriers. [ 32 ] These structures, alongside their linear analogues, have been broadly investigated for various applications in biomedicine.…”
Section: Introductionmentioning
confidence: 99%